IMPLEMENTATION OF NUMERACY LITERACY TRAINING FOR TEACHERS AND ITS ACHIEVEMENT IN CENTRAL MALUKU REGENCY - Palinussa, Anderson L; Laamena, Christina M; Talib, Taufan (Universitas Pattimura, 2023)
The achievement of learning outcomes from the 2022 public education report card issued by the Pusmendik Kemdibudristek at the elementary and junior high school levels for the Central Maluku Regency, obtained less than 50% have reached the minimum competency limit for reading and arithmetic literacy, this is below the minimum competency for literacy and numeracy skills. Therefore, it is essential for activities regarding the development of teacher quality in dealing with the learning process, especially in literacy and numeracy abilities. This service activity aims to provide benefits to teachers in implementing numeracy literacy in the learning process to improve student learning outcomes, especially in numeracy literacy skills. This service is carried out using a training method with stages: Exposure to numeracy-based learning, workshops on writing numeracy literacy questions, and evaluations. The service activity occurred at SMP Negeri 38 Maluku Tengah, which acted as a partner. The training was attended by 30 elementary and junior high school teachers throughout Central Maluku Regency. The evaluation was conducted to see the achievement of the activities. The results obtained an average of 90.92% during the implementation of service with planning and received a good appreciation from the participants, namely teachers in Central Maluku Regency